AN EMPIRICAL STUDY OF THE IMPACT OF ACTIVE LEADERSHIP ON EMPLOYEE’S JOB SATISFACTION IN THE SUBCONTRACTOR COMPANY - Reungrit, Jutharat; Praditbatuga, Piyathida; TREETIPBUT, Santhiti (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research aimed to identify the mediating role of adjusted expectations in the relationship between customer satisfaction and repurchase intention of sportswear retailer in UK. The target populations of this study were customers of online sportswear retailer in UK. The study employed the questionnaire method as a tool to collect data from 106 respondents. Single linear regression analysis was used to test research hypotheses. Results of hypothesis tests revealed that customer satisfaction influence online repurchase intention [R2 = .328, F = 50.220, p < .001]. Secondly, customer satisfaction influences adjusted expectations [R2 = .271, F = 38.354, p < .001]. Lastly, adjusted expectations influence online repurchase intention [R2 = .366, F = 58.907, p < .001]. To increase sportswear online customers, repurchase intention, sportswear online retailers should focus on improving the level of customer satisfaction and adjusted expectations toward online purchase.